Turbulent forced convection of nanofluid in an elliptic cross-sectional pipe - Selimefendigil, Fatih; Öztop, Hakan Fehmi; Ozgul, Ridvan (Pergamon-Elsevier Science Ltd, 2019)
In this study, numerical analysis of forced convection in a thee dimensional pipe with elliptic cross-section is considered by using CNT-water nanofluid as working fluid. Three dimensional steady flow and heat transfer equations with k- c turbulence model is solved by using finite element method. Effects of aspect ratio of elliptic cross-section and solid nanoparticle volume fraction on the heat transfer performance were analyzed. An experimental validation of the numerical study was performed and comparisons were made with other existing correlations for turbulent flow in a pipe. It was observed that significant enhancements in the heat transfer rate are achieved with the use of CNT nanoparticles which are in the range of 59% to 84% depending on the mass flow rate. The average Nusselt number deteriorates for higher values of aspect ratio in turbulent three dimensional configuration while the trends are similar for fluid and nanofluid. When the aspect ratio enhances from 0.5 to 1.67, approximately 53% reduction of average Nusselt number is obtained both for water and for nanofluid. Finally, a practical modeling strategy for estimating the average Nusselt number is proposed which uses linear interpolation among polynomial model coefficients for water and for nanofluid at the highest solid particle volume fraction.
Keywords: Carbon-nanotube nanofluids; Elliptic tube; Finite element method; 3D turbulent